(untitled) (Universal International Scientific Journal, 2026)
This thesis analyzes the psychological aspects of training future specialists in the process of globalization. The study highlights the need to use innovative methods to protect their mental health and prevent intellectual and emotional stress in the training of highly qualified personnel. Also, based on the theoretical views of Uzbek psychological scientists, the role of mental health in increasing the competitiveness of personnel is substantiated.